Utilization of Arbuscular Micorrhizal Fungi to Control Fusarium Wilt of Tomatoes - Theodorsius Pedai; Bambang Hadisutrisno; Achmadi Priyatmojo (Jurnal Perlindungan Tanaman Indonesia, 2015)
Tomato is a vegetable crop which is preferred by the Indonesian people. The problem encountered in tomato production is Fusarium wilt which is known as devastating disease. Studies have been done to solve the problem but effective and inexpensive control technique is still questioned. This study aimed to ascertain the ability of Arbuscular Mycorrhizal (AM) fungi as biological control agent in reducing tomato Fusarium wilt. Research was arranged in a completely randomized design (CRD) consisting of 5 treatments and 10 replications. The treatments were untreated plants, Fusarium oxysporum f.sp. lycopersici inoculated plants, AM fungi inoculated plants, AM fungi + F. oxysporum f.sp. lycopersici inoculated plants, F. oxysporum f.sp. lycopersici + benomyl inoculated plants. The results showed that plants which were inoculated with AM fungi had better growth compared to those which were not inoculated with AM fungi. Moreover, plants which were inoculated with AM fungi showed lower disease intensity compared to untreated plant and inoculated plant with F. oxysporum f.sp. lycopersici + benomyl application. Orthogonal contrast analysis showed plants treated with AM fungi significantly perform better growth and resistance towards infection compared with other treatments. Thus, it concluded that AM fungi had the potency as biological control agent.